2022
DOI: 10.1186/s12864-022-08383-1
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genomes of three Mangifera species, their genomic structure and gene transfer from chloroplast genomes

Abstract: Background Among the Mangifera species, mango (Mangifera indica) is an important commercial fruit crop. However, very few studies have been conducted on the Mangifera mitochondrial genome. This study reports and compares the newly sequenced mitochondrial genomes of three Mangifera species. Results Mangifera mitochondrial genomes showed partial similarities in the overall size, genomic structure, and gene content. Specifically, the genomes are circu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…These data suggest that the transfer events of ndh genes predated the degradation of ndh in the P. micranthum plastome, or there was more than one donor of their plastome origin sequences. Furthermore, most of the plastome origin genes have been nonfunctional pseudogenes in previous studies [ 3 , 4 , 40 , 42 ], except for a few cases—for instance, psaA , ndhB , and rps7 in H. cannabinus [ 56 ] and petN , psaA , atpI , trnI-CAU , and trnC-GCA in Mangifera [ 63 ]. The mitogenome of P. micranthum contained 44 genes from plastid origin, and 12 of these genes are intact and potentially functional ( ycf4 , cemA , petA , rbcL , rpoA , rpl36 , ndhJ , psbE , psbF , psbJ , psbL , and atpE ), which has been rather rare in previous studies ( Table 2 and Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the transfer events of ndh genes predated the degradation of ndh in the P. micranthum plastome, or there was more than one donor of their plastome origin sequences. Furthermore, most of the plastome origin genes have been nonfunctional pseudogenes in previous studies [ 3 , 4 , 40 , 42 ], except for a few cases—for instance, psaA , ndhB , and rps7 in H. cannabinus [ 56 ] and petN , psaA , atpI , trnI-CAU , and trnC-GCA in Mangifera [ 63 ]. The mitogenome of P. micranthum contained 44 genes from plastid origin, and 12 of these genes are intact and potentially functional ( ycf4 , cemA , petA , rbcL , rpoA , rpl36 , ndhJ , psbE , psbF , psbJ , psbL , and atpE ), which has been rather rare in previous studies ( Table 2 and Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, P. micranthum had fewer repeat sequences, both in number and relative percentage compared to other monocot species tested [ 5 ]. Further, the number of repeat sequences (2%) was relatively less than most other species, e.g., Mangifera (3.5% to 4.5%) [ 63 ], Monsonia (3.9% to 6.9%) [ 68 ], Trifolium (6.6% to 8.6%) [ 72 ], and Silene vulgaris (18.8 to 28%) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dimer repeats were the most abundant SSR type (about 48%) in the Actinidia mitogenome ( Figure 2 C), which is commonly found in Suaeda glauca [ 67 ]. Gene transfer from the chloroplast to the mitogenome frequently occurs during long-term plant evolution [ 68 ]. A total of 9–55 kb of plastid-derived sequences was observed, which occupied 3–6% of the Actinidiaceae mitogenomes ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of RNA editing sites varies in different species [ 72 ]. Previous studies identified approximately 491 RNA editing sites within 34 genes in rice [ 68 ] and 486 RNA editing sites within 31 genes in Primula vulgaris [ 73 ]. In Actinidiaceae, the number of RNA editing sites in most PCGs was extremely conserved in Actinidiaceae, similar to other plant studies [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitogenome sequences of angiosperms generally have one or more pairs of large non-tandem repeats that can act as sites for inter- and intramolecular recombination, leading to multiple alternative arrangements within a species (isoforms, including subgenomic forms) [ 16 ]. Although plant mitogenomes are often assembled and displayed as circular maps (e.g., [ 36 ]), plant mtDNA most likely does not exist as one large circular DNA molecule, but mostly as a complex and dynamic collection of linear DNA with combinations of smaller circular and branched DNA molecules [ 3 , 11 , 15 – 17 , 37 43 ].…”
Section: Introductionmentioning
confidence: 99%